Understanding the Mechanobiology of Gliosis May Be the Key to Unlocking Sustained Chronic Performance of Bioelectronic Neural Interfaces. Issue 3 (19th December 2021) - Vallejo-Giraldo, Catalina; Krukiewicz, Katarzyna; Biggs, Manus Jonathan Paul
Abstract : In an effort to develop the next generation of neural implants, current research has focused on solving the challenges associated with the foreign body reaction and promoting long‐term device performance in vivo. Although the cutting edge of research in this field appears to be moving away from traditional metallic and semiconductor materials, the complex tissue dynamics which occur at the electrode–neural interface following device implantation are yet to be resolved. In particular, understanding the molecular processes of gliosis and the onset and persistence of scar formation is key in developing stable and specific neural recording/stimulation devices. Critically, it is recognized that neural device implantation leads to a significant disruption of tissue integrity at the peri‐electrode site. Accordingly, an in‐depth understanding of mechanotransduction in neuronal cell populations at the peri‐implant region is required to better inform neural interface design. This perspective highlights the need for a comprehensive mechanobiological understanding of gliosis to enhance the development of neural implants with improved chronic functionality. Abstract : An in‐depth understanding of mechanotransduction in neuronal cell populations at the peri‐implant region is required to better inform neural interface design. Thus, this perspective highlights "the need" for a comprehensive mechanobiological understanding of gliosis from the role of extracellular matrix (ECM) to the mechanoresponsive ion channels to enhance the development of neural implants with improved chronic functionality.